Intravenous Sotalol - Reintroducing a Forgotten Agent to the Electrophysiology Therapeutic Arsenal - Batul, Syeda Atiqa (J Atr Fibrillation, 2017)
Sotalol is a racemic mixture possessing beta-blocker and class III anti arrhythmic properties. Approved by US food and drug administration (FDA) since 2009 based on its bioequivalence with oral sotalol, clinicians are less familiar with the potential uses of the intravenous form despite its re-launch in United States in 2015. Available literature suggests that intravenous sotalol in recommended doses can be safely administered in adult and pediatric population achieving rapid reliable therapeutic plasma concentration and without additional proarrhythmic effects when compared to its oral form as well as other antiarrhythmic medications. Intravenous sotalol may have potential uses as an alternative agent for highly symptomatic atrial fibrillation post cardiac surgery as well as in life threatening ventricular arrhythmias. As with its oral form, judicious use with close attention to QTc and renal function is warranted. Further studies are needed to better understand the safety, efficacy and different dosing regimens of parenteral sotalol in adults and children.